Pengaruh Leverage, Firm Size dan Cash Holding Terhadap Manajemen Laba Perusahaan Dalam Perspektif Ekonomi Islam - Tri Novita Sari; Rosydalina Putri; Siska Yuli Anita (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to partially and simultaneously analyze the influence of leverage, firm size and cash holding on profit management in property and real estate companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The research method used is quantitative research. The source of the data is secondary data. The data analysis used was panel data regression analysis using the help of the Eviews version 10 program. The population in this study is property and real estate sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sample after selection was 17 companies in the 2019-2023 period, totaling 85 observation data. The results of this study show that partially Leverage and Cash Holding have no effect on profit management. Meanwhile, Firm Size has a significant negative effect on profit management. Simultaneously, Leverage, Firm Size and Cash Holding have a significant positive effect on profit management.